FRI0471 The Value of Repeated Nailfold Videocapillaroscopy in Raynaud's Phenomenon in Daily Practice: A Follow-Up Study in the Netherlands. (9th June 2015) - de Boer, B.; Meijs, J.; van Aken, J.; Steup-Beekman, M.; Huizinga, T.; Schouffoer, A.; de Vries-Bouwstra, J.
Abstract : Background: Nailfold videocapillaroscopy (NVC) visualizing microvascular damage is an important tool to differentiate Raynaud's phenomenon (RP) into primary RP (PRP) and secondary RP (SRP) (1). Based on possible transition from PRP to SRP (semi)annual NVC has been advocated to detect transition to SRP as early as possible (1-3). Whether standardized (semi)annual NVC should be implemented in clinical practice is unknown. Objectives: To evaluate the additive diagnostic value of repeated NVC after one year in patients with RP. Methods: Patients with RP who underwent NVC at the outpatient clinic at least six months ago and did not have a definite diagnosis were invited for follow-up NVC. PRP was defined according to the definition of LeRoy (4); SRP was defined as RP associated with a connective tissue disease fulfilling applicable diagnostic criteria; the remaining patients were classified as suspected SRP (sSRP). The number of patients in which follow-up NVC resulted in change of diagnosis was determined. Results: In total 107 patients with RP underwent NVC. Of these71 underwent follow-up NVC after a mean period of 12 months (range 6-25 months). At baseline, eight (11%) patients had PRP, 28 (40%) SRP and 35 (49%) sSRP. The rate of progression from PRP to SRP was 12.5% (one of eight patients). The rate of progression from sSRP to SRP was 3% (one of 35 patients). NVC pattern had changed in 21 (30%) patients: six (8%) worsened and 15 (21%) improved. In total five patients (7%) had a different diagnosis at follow-up, two of which based on clinical symptoms, three based on NVC pattern only: one changed from PRP to SRP, based on development of sclerodactyly, one changed from sSRP to SRP based on biopsy proven myositis, and three patients changed from sSRP to PRP due to normalization of NVC. Thus, NVC contributed to change in diagnosis in three out of 43 patients (7%) with PRP or sSRP, all improving from sSRP to PRP. Conclusions: Although progression from PRP to SRP was observed in 12.5% and progression from sSRP to SRP in 3%, changes in NVC did not contribute to change in clinical diagnosis in these patients. Based on the findings of this study, a follow-up NVC after one year in patients with PRP or sSRP without a change in clinical symptoms cannot be advocated. Extended follow-up in a larger population is needed to confirm this observation. References: Cutolo M, Smith V. State of the art on nailfold capillaroscopy: a reliable diagnostic tool and putative biomarker in rheumatology? Rheumatology 2013;52(11):1933-40. Cutolo M, Pizzorni C, Sulli A. Identification of transition from primary Raynaud's phenomenon to secondary Raynaud's phenomenon by nailfold videocapillaroscopy: comment on the article by Hirschl et al. Arthritis Rheum 2007;56(6):2102-3. Hirschl M, Hirschl K, Lenz M, Katzenschlager R, Hutter HP, Kundi M. Transition from primary Raynaud's phenomenon to secondary Raynaud's phenomenon identified by diagnosis of an associated disease: results of ten years of prospective surveillance. Arthritis Rheum 2006;54(6):1974-81. LeRoy EC, Medsger TA, Jr. Raynaud's phenomenon: a proposal for classification. Clin Exp Rheumatol 1992;10(5):485-8. Disclosure of Interest: B. de Boer: None declared, J. Meijs Grant/research support from: J. Meijs was supported by an unrestricted educational grant of Actelion Pharmaceuticals Nederland BV (Woerden, The Netherlands)., J. van Aken: None declared, M. Steup-Beekman: None declared, T. Huizinga: None declared, A. Schouffoer: None declared, J. de Vries-Bouwstra: None declared